2021
DOI: 10.1093/eurheartj/ehab444
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve derived from computed tomography coronary angiography in the assessment and management of stable chest pain: the FORECAST randomized trial

Abstract: Aims  Fractional flow reserve (FFRCT) using computed tomography coronary angiography (CTCA) determines both the presence of coronary artery disease and vessel-specific ischaemia. We tested whether an evaluation strategy based on FFRCT would improve economic and clinical outcomes compared with standard care. Methods and results  Overall, 1400 patients with stable chest pain in 11 centres were randomized to initial testing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 28 publications
5
59
0
1
Order By: Relevance
“…Additionally, the recent FORECAST (Fractional Flow Reserve Derived From Computed Tomography Coronary Angiography in the Assessment and Management of Stable Chest Pain) trial of over 1400 patients, while referral to invasive angiography was lower, the use of FFR-CT did not demonstrate any benefits in terms of healthcare costs, cardiovascular outcomes, or quality of life compared to CT-alone [ 10 ]. Similarly, the recent RAPID-CT (Rapid Assessment of Potential Ischaemic Heart Disease with CTCA) trial [ 11 ] included 1748 patients with intermediate risk with suspected or a provisional diagnosis of acute coronary syndrome randomised to Early CCTA and standard of care compared with standard of care only. The study demonstrated that early CCTA did not alter overall coronary therapeutic interventions or one-year clinical outcomes.…”
Section: Disagreement With Some Aspects Of the Guidelinesmentioning
confidence: 99%
“…Additionally, the recent FORECAST (Fractional Flow Reserve Derived From Computed Tomography Coronary Angiography in the Assessment and Management of Stable Chest Pain) trial of over 1400 patients, while referral to invasive angiography was lower, the use of FFR-CT did not demonstrate any benefits in terms of healthcare costs, cardiovascular outcomes, or quality of life compared to CT-alone [ 10 ]. Similarly, the recent RAPID-CT (Rapid Assessment of Potential Ischaemic Heart Disease with CTCA) trial [ 11 ] included 1748 patients with intermediate risk with suspected or a provisional diagnosis of acute coronary syndrome randomised to Early CCTA and standard of care compared with standard of care only. The study demonstrated that early CCTA did not alter overall coronary therapeutic interventions or one-year clinical outcomes.…”
Section: Disagreement With Some Aspects Of the Guidelinesmentioning
confidence: 99%
“…In addition to the unique ability for non-invasive qualitative and quantitative evaluation of coronary atherosclerotic plaque, CCTA can provide functional information without the increased burden of radiation exposure and administration of stress agents. Compared with conventional CCTA alone, it has been demonstrated that CT-FFR had improved discrimination of ischemia (33) the 9-month costs of patients with stable angina in the CT-FFR group were slightly higher than that in the routine care group, but the difference was not significant (p = 0.10) (34).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in a sub-study of the PROSPECT trial, a A novel CT feature is the measurement of fractional flow reserve. This provides additional information on the hemodynamic effects of coronary plaques and is able to reduce the need for invasive coronary angiography after CTCA [117]. The role of fractional flow reserve for the detection of vulnerable plaques seems questionable, since most ACS arises from non-significant coronary plaques.…”
Section: Computed Tomography Coronary Angiographymentioning
confidence: 99%